Analysis of Student Perceptions on Blended Learning Using Learning Management System (LMS) for Physical Education, Sports, and Health Courses - Rustam, R.; Lince, Ranak; Kusmaladewi, K.; Halim, Patmawati; Ahmar, Ansari Saleh; Rahman, Abdul; Rusli, R. (JOIV : International Journal on Informatics Visualization, 2025)
This study investigates student perceptions of LMS-based Blended Learning in Physical Education, Sports, and Health subjects at Public Junior High School 25 in Barru Regency, South Sulawesi, Indonesia. A descriptive quantitative design was utilized for this research. Probability sampling was employed to ensure representativeness. Data was collected through a structured questionnaire consisting of twenty- five items designed to measure four key aspects of LMS- based blended learning: e- learning knowledge, e- learning accessibility, e- learning usefulness, and e- learning usage satisfaction. The reliability of the questionnaire was confirmed via Cronbach's α, which produced a value of 0 830, and McDonald's ω, yielding a value of 0 0.850, indicating strong internal consistency and reliability of the instrument. Results showed that 82. 55% of respondents agreed or strongly agreed that e- learning knowledge is vital for supporting blended learning, suggesting awareness and confidence among students regarding the role of digital learning tools in enhancing their educational experiences. Additionally, 61. 61.41% agreed or strongly agreed that e- learning accessibility significantly aids the implementation of blended learning, emphasizing that easy access to LMS platforms is crucial for student engagement. Furthermore, 60. 16% acknowledged the importance of e- learning usefulness in the current educational landscape, highlighting a widespread recognition of digital tools' significance in education. Lastly, 53. 83% stated satisfaction with e- learning usage is a key factor influencing successful blended learning experiences. These findings indicate a favorable perception among students toward LMS-based blended learning in physical education, sports, and health subjects. The study emphasizes the importance of e- learning knowledge, accessibility, usefulness, and satisfaction for creating effective blended learning environments. Further research is suggested to examine the long-term effects of LMS-based blended learning on student outcomes across diverse educational settings.